Successful minimally invasive surgery for postpartum retroperitoneal hematoma complicated by an infection: Two case reports. (November 2021) - Yokoe, Takuya; Kita, Masato; Fukuda, Hisato; Butsuhara, Yusuke; Sumi, Genichiro; Okada, Hidetaka
Abstract: Introduction: and importance Postpartum retroperitoneal hematoma is a birth canal injury that is difficult to diagnose because of its invisibility. Secondary infections of these hematomas are rare, and their diagnostic and management strategies have not been fully elucidated. We present two cases of postpartum retroperitoneal hematomas with infection, which were successfully treated with minimally invasive surgery. Case presentation: Case 1 was of a 2X-year-old woman who presented with complaints of fever; a provisional diagnosis of chorioamnionitis and Streptococcus pyogenes -induced sepsis was made. Case 2 was of a 3X-year-old woman who underwent uterine artery embolization and manual removal of the placenta for suspected placenta accreta. Both cases were diagnosed with adnexal hematomas, and antibiotic therapy failed in both patients. Therefore, we performed exploratory laparoscopy and made a diagnosis of retroperitoneal hematomas with infection; laparoscopic drainage resulted in rapid resolution of the clinical symptoms and abnormal blood test results. Clinical discussion: Once an abscess develops, antibiotic treatment has a limited effect, and surgical drainage should be performed. Management of retroperitoneal hematomas is difficult, especially when complicated by an infection. Conclusion: Minimally invasive procedures involving laparoscopy could be beneficial for the management of postpartum retroperitoneal hematomas complicated by an infection. Highlights: Postpartum retroperitoneal hematoma is difficult to diagnose. Secondary infections of these hematomas are rare. The diagnosis and management strategies have not been fully elucidated. Management of retroperitoneal hematomas complicated by infection is challenging. Laparoscopy helps manage postpartum retroperitoneal hematomas with infection.